How to Surgically Remove the Permanent Mesh Ring after the Onstep Procedure for Alleviation of Chronic Pain following Inguinal Hernia Repair - Stina Öberg; Kristoffer Andresen; Jacob Rosenberg (Case Reports in Surgery)
A promising open inguinal hernia operation called Onstep was developed in 2005. The technique is without sutures to the surrounding tissue, causing minimal tension. A specific mesh is used with a memory recoil ring in the border, which may cause pain superficial to the lateral part of the mesh for slender patients. The aim of this study was to illustrate an easy procedure that alleviates/removes the pain. A male patient had persistent pain six months after the Onstep operation and therefore had a ring removal operation. The procedure is presented as a video and a protocol. At the eleven-month follow-up, the patient was free of pain, without a recurrence. It is advised to wait some months after the initial hernia repair before removing the ring, since the mesh needs time to become well integrated into the surrounding tissue. The operation is safe and easy to perform, which is demonstrated in a video.